2016
DOI: 10.1007/s10936-016-9432-4
|View full text |Cite
|
Sign up to set email alerts
|

Spoken Language Activation Alters Subsequent Sign Language Activation in L2 Learners of American Sign Language

Abstract: A large body of literature has characterized unimodal monolingual and bilingual lexicons and how neighborhood density affects lexical access; however there have been relatively fewer studies that generalize these findings to bimodal (M2) second language (L2) learners of sign languages. The goal of the current study was to investigate parallel language activation in M2L2 learners of sign language and to characterize the influence of spoken language and sign language neighborhood density on the activation of ASL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This study extends previous studies that have shown positive effects of proficient sign language knowledge on the acquisition of written English (e.g., Mayberry, Del Giudice, & Lieberman, 2011). Additionally, the present results show an interdependence of two language modalities at the lexical level, which has been hypothesized previously by researchers studying the bimodal bilingual lexicon (Giezen & Emmorey, 2016; Shook & Marian, 2012; Williams & Newman, 2016a, in press).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study extends previous studies that have shown positive effects of proficient sign language knowledge on the acquisition of written English (e.g., Mayberry, Del Giudice, & Lieberman, 2011). Additionally, the present results show an interdependence of two language modalities at the lexical level, which has been hypothesized previously by researchers studying the bimodal bilingual lexicon (Giezen & Emmorey, 2016; Shook & Marian, 2012; Williams & Newman, 2016a, in press).…”
Section: Discussionsupporting
confidence: 88%
“…A vocabulary test from Williams and Newman (in press) was used to capture growth in ASL lexical knowledge. This variable was obtained by administering an ASL vocabulary test twice, once before ASL instruction (T0) and again after one semester of instruction (T1).…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Previous studies on M2L2 adult learners have shown that they do transfer gestural handshapes in spoken language to sign language (i.e., transfer phonological information), for example, handshape between M1L1 (their spoken first language) and M2L2 (the sign language being learned) (see for example Chen Pichler, 2011;Chen Pichler & Koulidobrova, 2016;Williams & Newman, 2017;Beal, 2020;Marshall, Bel, Gulamani & Morgan, 2020). These handshapes come from gestures that co-occur with spoken language and are different from handshapes in lexical signs, leading to an incorrect production of the lexical sign, i.e., the sign YES in ASL made with "fist" handshape instead of using the S handshape (Chen Pichler & Koulidobrova, 2016).…”
Section: Language Learning (M2l2)mentioning
confidence: 99%
“…According to Williams et al [34], a bifurcation of neighborhood density based on sublexical features reveals perceptual differences for the form and location. They mention Carreiras et al [35], and their findings in lexical access of Spanish Sign Language and its density as perceived by the deaf.…”
Section: Perceptual Differencesmentioning
confidence: 99%